A Group of Geoglyphs in the Lower Carabamba Valley, Northern Peru. Issue 3 (September 2022) - Sghinolfi, Amedeo; Millaire, Jean-François; Navarro Vega, Jeisen; La Torre Calvera, Estuardo
Abstract : In 2019, while conducting a survey of the Carabamba River valley (ca. 150–3, 325 m asl) in northern Peru, we identified and surveyed a group of five unreported geoglyphs. Their location and iconography suggest that they date from the Formative period (1800–200 BC) and that they were possibly associated with a form of fertility ritual.